Studi Fenomenologis: Eksplorasi Makna Konformitas Pada Anggota Organisasi Ikatan Mahasiswa Boyolali - Az Zahra, Ummu Hafadzoh; Hikmah, Soviyatun Nur; Bahrudin, Maulana Azis; Azizah, Alya; Anas, Siti Hikmah (Universitas Paramadina, 2025)
Conformity often arises in student organizations when individuals adjust to group norms to gain social acceptance, including in the Boyolali Student Association (IMB), which has a distinctive regional and cultural identity. This phenomenon attracts further attention because it can demonstrate the social dynamics formed from the intersection of group norms and cultural identity. This study aims to explore the meaning of conformity among members of the Boyolali Student Association (IMB) with four subjects aged 18–25 years selected through purposive sampling according to the criteria of active members. The method used is qualitative phenomenological through semi-structured interviews and Descriptive Phenomenological Analysis (DPA). The results show conformity reflected through cohesiveness, agreement, and obedience. Overall, conformity in the Boyolali Student Association (IMB) is adaptive and supports group stability.